Pengukuran Rasio Keuangan Terhadap Penghindaran Pajak Menggunakan Profitabilitas, Leverage, Likuiditas dan Ukuran Perusahaan - Setyapurnama, Yudi Santara (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Tax avoidance is a phenomenon that is often carried out by companies to minimize their tax burden legally. Although not against the law, this behavior has various implications for the government, shareholders, and business sustainability. The urgency of studying tax avoidance lies in its impact on state revenues, legal risks for companies, and conflicts of interest between management and owners from an agency theory perspective. The sample used in the study was 13 manufacture sector companies listed on the IDX, the research period was 2020 - 2024 with a purposive sampling technique. The study used a multiple linear regression analysis model. The results of the study showed that Return on Assets (ROA), Current Ratio (CR), and Company Size had an effect on tax avoidance. While Leverage had no effect on tax avoidance. Simultaneously, the variables in the study had an effect on tax avoidance.